THE EFFECT OF BIOSTIMULANTS AT DIFFERENT RATES ON THE YIELD OF REPLANTED OILSEED SUNFLOWER - Yuldasheva Zulfiya Kamalovna; Karabaeva Dilfuza Jo‘raevna (Journals Park Publishing, 2023)
Microfertilizers, biostimulants, microfertilizers and growth substances contained in the immunostimulant have been found to have a positive effect on the growth, development and formation of seeds in the basket of sunflower of the local Dilbar variety, on the weight of 1000 seeds and on the yield. The use of MERS microfertilizer made it possible to increase the productivity of one plant by 362.9-430.4 grams, the use of Fitovak immunostimulant by 288.1-388.0 grams, and the use of Biodux biostimulant by 107.7-287.7 grams.
Keywords: sunflower, biostimulant, standard, immunostimulant, microfertilizer, norm, yield, growth, development.